2011
DOI: 10.1016/j.jhazmat.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Particle-phase dry deposition and air–soil gas exchange of polycyclic aromatic hydrocarbons (PAHs) in Izmir, Turkey

Abstract: a b s t r a c tAmbient air and dry deposition samples were collected at suburban and urban sites in Izmir, Turkey. Atmospheric total (particle + gas) 14 PAHs concentrations were 36 ± 39 and 144 ± 163 ng m −3 for suburban and urban sites, respectively. Phenanthrene was the most abundant compound at all sites, and all samples were dominated by low molecular weight PAHs. Average particulate 14 PAH dry deposition fluxes were 8160 ± 5024 and 4286 ± 2782 ng m −2 day −1 and overall average particulate dry deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…There was a decrease of the dry deposition velocity with the increase of PAH MW in this study. The results, in line with the previous findings, indicated that a greater fraction of the high MW PAHs were associated with fine particles rather than to the low MW PAHs (Demircioglu et al, 2011;Tasdemir and Esen, 2007).…”
Section: Dry Deposition Velocities and Washout Ratiosupporting
confidence: 92%
“…There was a decrease of the dry deposition velocity with the increase of PAH MW in this study. The results, in line with the previous findings, indicated that a greater fraction of the high MW PAHs were associated with fine particles rather than to the low MW PAHs (Demircioglu et al, 2011;Tasdemir and Esen, 2007).…”
Section: Dry Deposition Velocities and Washout Ratiosupporting
confidence: 92%
“…Since large particles dominate the atmospheric dry deposition, higher deposition velocities were attributed to larger particles from resuspension of polluted soil, dust particles from paved/ unpaved roads, and non-vegetated areas at the suburban site. Relatively smaller dry deposition velocities that were (Cetin and Odabasi, 2007b;Bozlaker et al, 2008a, b;Bozlaker et al, 2009;Demircioglu, 2011b) with fine PM fractions determined in the present study.…”
Section: Implications For Atmospheric Fate and Transportsupporting
confidence: 48%
“…Recently, dry deposition velocities of POPs in suburban sites were found to be higher than those measured for Urban and/or Industrial sites (Cetin and Odabasi, 2007b;Demircioglu et al, 2011b). This spatial difference in deposition velocities may be due to different size distributions of urban/industrial and suburban particles.…”
Section: Implications For Atmospheric Fate and Transportmentioning
confidence: 94%
See 1 more Smart Citation
“…Analysis Procedure: For pre-treatment procedure, soil, lichen or pine needle samples were weighed and dried with lyophilizator, and they were subjected to ultrasonic extraction. Clean up stage was made with alumina-silicic acid column [4]. The samples analyzed in GC-MS. Total deposition samples extracted by liquid-liquid extraction with hexane.…”
Section: Methodsmentioning
confidence: 99%